Alpine steppe degradation weakens ecosystem multifunctionality through the decline in climax dominant species on the Qinghai-Tibetan plateau - Wang, Xiao-Yun; Xiao, Yuan-Ming; Wang, Wen-Ying; Yang, Xin-Yu; Zhou, Guo-Ying (Frontiers in Plant Science, 2025)
IntroductionThe diversity and dominant species of plant communities are vital for maintaining grassland ecosystem multifunctionality. However, grassland degradation can disrupt plant community diversity, dominant species, and their linkages with ecosystem multifunctionality. MethodsWe studied the alpine steppe in the Qinghai Lake Basin, conducting plant community surveys and sampling at 15 sites across four degradation gradients (non-degraded, lightly degraded, moderately degraded, and severely degraded). This study investigated the relationships among plant community diversity, dominance of dominant species, and ecosystem multifunctionality (derived via factor analysis from 11 indicators: aboveground biomass, belowground biomass, plant height, coverage, TN, TP, AN, AP, SOC, SM, and pH) in the context of alpine steppe degradation. ResultsThe results revealed that plant community diversity-measured using the Shannon-Wiener index, Simpson index, species richness, and Pielou evenness index—followed a unimodal trend with increasing degradation, peaking at moderate degradation levels. Meanwhile, belowground biomass, soil nutrient and moisture content declined significantly with degradation severity. Regression analysis revealed that alpine steppe ecosystem multifunctionality followed a binomial rather than linear relationship with plant diversity and dominance of dominant species across degradation gradients. In non-degraded and moderately degraded alpine steppe, ecosystem multifunctionality responded significantly to Shannon-Wiener index, Simpson index, and species richness, but not to Pielou evenness. During the degradation process of alpine steppe, the linear mixed model results demonstrated that the dominance of dominant species significantly influenced ecosystem multifunctionality.DiscussionConsequently, in the ecological restoration of degraded alpine steppe, precedence should be accorded to the establishment of dominant species and the enhancement of soil conditions, subsequently followed by the optimization of plant community diversity.